Social development and participation - Niraj Kumar (2006)
In recent discussions the notion of social development has been detached from the evolutionary hypothesis and has focused on the questions of the satisfaction of human needs and improvement in the quality of life. The concept of social development is more comprehensive than economic development. On the other hand people's participation in any programme from above is involvement and from below it is empowerment. This is the documentation of some of the ongoing social development programmes in different parts of the country whose success lies in the participation of beneficiaries in the programme from below. Through their participation in different development programmes, the beneficiaries get empowered and subsequently their quality of life improves. At the end, the paper also tries to examine the essential ingredients necessary for replication of these successful models in other parts of the country. - Reproduced.
Keywords: Economic and social development